2022
DOI: 10.1002/cjce.24606
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis‐based microbial enhanced oil recovery (MEOR) in polymer microfluidic chip

Abstract: Microbial enhanced oil recovery (MEOR) is a tertiary oil recovery process that manipulates the microbial environment inside oil reservoirs to modify the physical/chemical properties of the reservoirs to enhance the oil recovery. Up to now, the detailed MEOR mechanism is still not entirely clear due to the multiple influence factors (e.g., pH, nutrients, temperature, porosity, and permeability) on microbial growth and reproduction, as well as the lack of understanding of microbial's influencing mechanism on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…As a result, the oil recovery was enhanced by 19%, providing valuable new insights and a theoretical foundation for applying microbial oil displacement techniques. Liu et al [202] carried out a Bacillus subtilis-based MEOR process using a microfluidic device made of polymethyl methacrylate to mimic the MEOR process in reservoirs, which demonstrated that the ex situ MEOR process with B. subtilis achieved a recovery rate of 38.56%, while the in situ MEOR process achieved a recovery rate of 40.27%. This research provided a novel tool for comprehending the MEOR process, offering advantages in visibility and precise fluid control during the MEOR process.…”
Section: Microscopic Oil Displacing Process Of Microbial Consortiummentioning
confidence: 99%
“…As a result, the oil recovery was enhanced by 19%, providing valuable new insights and a theoretical foundation for applying microbial oil displacement techniques. Liu et al [202] carried out a Bacillus subtilis-based MEOR process using a microfluidic device made of polymethyl methacrylate to mimic the MEOR process in reservoirs, which demonstrated that the ex situ MEOR process with B. subtilis achieved a recovery rate of 38.56%, while the in situ MEOR process achieved a recovery rate of 40.27%. This research provided a novel tool for comprehending the MEOR process, offering advantages in visibility and precise fluid control during the MEOR process.…”
Section: Microscopic Oil Displacing Process Of Microbial Consortiummentioning
confidence: 99%